ANALISIS KINERJA EKONOMI GLOBAL DAN MAKROEKONOMI DOMESTIK TERHADAP PASAR MODAL SYARIAH INDONESIA - Retnasih, Nora Ria (UIN Sayyid Ali Rahmatullah Tulungagung, 2019)
The fluctuations of Islamic stock indexes incorporated in the Jakarta Islamic Index (JII) is influenced not only by domestic factors but also global economic conditions. This study aims to examine the relationship between global economic variables (FFR and DJI) and domestic macroeconomic conditions (exchange rates and inflation) towards the movement of the Islamic stock index (JII) in both the short and long term. This type of quantitative research uses the Vector Autoregressive (VAR) method with the Impulse Response Function (IRF) and Forecast Error Decomposition of Variance (FEDV) tests. The data used is monthly, starts from January 2014 to December 2017. The IRF test results show that the FFR and DJI variables are responded positively by JII both in the short and long term. The exchange rate variable is responded to negatively in the short and medium term but has changed positively in the long run. Meanwhile, the inflation variable was responded negatively during the study period. Overall, the FEDV test shows that the four variables contribute to the JII, with the largest contribution given by domestic variables (exchange rates and inflation).